Sexo e poder: violência sexual no âmbito doméstico e conjugal-Vitória (ES): agosto de 2006-agosto de 2009 - Caminoti, Jacqueline Medeiros (2015)
The research “Sex and power: sexual violence in domestic and marital context. Vitória (ES) – august 2006- august 2009” analyzes sexual violence within the domestic and marital context, establishing causal links between this type of violence and male domination. Were used as documentary sources 112 police reports recorded in the Police Station Specialized in Assistance to Women (Delegacia Especializada em Atendimento à Mulher - DEAM) in Vitória (ES), between August 2006, when it enters into force of Law No. 11,340, known as the Maria da Penha Law whose goal is to protect women from various types of domestic and family violence, including sexual,and 2009, due to the change of the wording of articles that deal with violence against sexual freedom of the Brazilian Penal Code, which took place that year